Are Non-Linear Dynamics A Universal Occurrence? Further Evidence From Asian Stock Markets - Lim, Kian-Ping; Azali, M.; Habibullah, M.S.; Liew, Venus Khim-Sen (Munich University Library, 2003)
With abounding evidence of non-linearity in stock markets of developed markets, this study attempts to narrow the gap in the literature of Asian countries by providing further empirical evidence to the issue “are non-linear dynamics a universal occurrence?”. The results from the Hinich bispectrum test indicate strong evidence of non-linearity in all the Asian stock markets under investigate- Japan, Hong Kong, Singapore and Malaysia. These findings further add to the empirical support that nonlinearity is a salient feature in stock market time series data and have important implications for works on market efficiency, modelling and pricing and hedging strategies in derivatives markets.